Creative urban kampung based on local culture, a case of Kampung Bustaman Semarang - Yuliastuti, Nany; Sukmawati, Annisa Mu'awanah (Journal of Architecture and Urbanism, 2020)
Urban kampung has the uniqueness and becomes the historical development of the city. Urban kampung has local culture, which potentially purposes to create a creative urban kampung. Kampung Bustaman in Semarang City allegedly has some local asset to develop towards a creative kampung by using its local culture. This study employed a qualitative method through a qualitative descriptive analysis to formulate the creative kampung concept on Kampung Bustaman. The findings show that Kampung Bustaman has local culture as local assets – goat processing and culinary related to goat. Local community assisted by the other parties and local institution should develop these local assets to enhance the local economy and strengthen social ties. It can be realized by food processing to be more valuable, kampung events, and art. A strong commitment of community is required to ensure the creative activities and promote creative urban kampung. It concludes that creative kampung is a kampung that can optimize its local assets for communities’ welfare of through creative ideas.